PEMANFAATAN MANURE HASIL DEGRADASI LARVA LALAT HITAM (Hermetia illucens L) SEBAGAI PENGGANTI TEPUNG IKAN TERHADAP PENAMPILAN AYAM BURAS FASE GROWER - Simboh, Elvis N.; Manangkot, H.J.; Lambey, L.J.; Tangkau, L.M.S. (Universitas Sam Ratulangi, 2017)
UTILIZATION MANURE DEGRADED USING BLACK FLY LARVAE (Hermetia illucens L) SUBSTITUTING FISH MEAL IN RATION ON LOCAL GROWING CHICKENThe objective of this study was to evaluate the performance of local growing chicken fed ration containing manure flour degraded (MFD) by Larva of black fly (Hermetia illucens L). This experiment was carried out using a complete Randomized Design (RAL), consisted of 4 treatments and five replications in each treatment as follows: R0 = Rations with 15% fish meal + 0% MFD, R1 = 10% fish meal + 5% MFD, R2 = 5%Â fish meal + 10% MFD, and R3 = 0% fish meal + 5% MFD. The variables measured were feed consumption, average daily gain and feed efficiency. Statistical analysis was done according to the procedure using analysis of variance. Results obtained in the research showed that treatments did not affected significantly feed consumption, average daily gain and feed efficiency of local grower chicken. Therefore, it can be concluded that MFD can be used as the candidate ingredient replacing fish meal in ration of the local grower chicken.Key words: Manure flour degraded, fish meal, black fly, kampong growing chicken